Pengaruh Berbagai Tingkat Konsentrasi Aditif Gula Merah, EM4 (Effective Microorganism) dan Dedak terhadap Kualitas Uji Organoleptik Silase Jerami Jagung - Slamet Laharjo; Kastalani Kastalani; Herlinae Herlinae (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2022)
This study aims to determine the effect of various levels of additive mixture of brown sugar, EM4 (Effective microorganism) and bran on the quality of corn straw silage. This research was conducted using a completely randomized design with 4 treatments and 5 replications. Treatment A = Brown Sugar 3% + EM4 2% + Bran 0%, B = Brown Sugar 6% + EM4 2% + Bran 4 %, C = Brown Sugar 9% + EM4 2% + Bran 8% and D = Brown Sugar 12% + EM4 2% + Bran 12%. Observations were made using the organoleptic method which included odor, color, texture, and fungus. The results showed that the addition of brown sugar, EM4 and bran additives did not significantly affect the quality of the organoleptic test of baud and color of corn straw silage but had a very significant effect on the quality of the organoleptic texture and fungus test of corn straw silage. Addition of 12% brown sugar, 2% EM4 and 12% bran additives resulted in the best quality for the organoleptic test of corn straw silage and fungi. Keywords: Corn straw silage, brown sugar, rice bran